2018
DOI: 10.2147/ott.s190333
|View full text |Cite
|
Sign up to set email alerts
|

Use of anlotinib in intra-abdominal desmoplastic small round cell tumors: a case report and literature review

Abstract: BackgroundIntra-abdominal desmoplastic small round cell tumor (IADSRCT) is a highly invasive malignant tumor that is rare in clinical practice. Anlotinib is a multitarget receptor tyrosine kinase inhibitor which inhibits vascular endothelial growth factor receptor (VEGFR) 1–3, fibroblast growth factor receptor (FGFR) 1–4, platelet-derived growth factor receptors (PDGFR) α/β, c-Kit, and Met. In our study, we present a record of IADSRCT which was validly treated by anlotinib.Case presentationA 38-year-old man wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 19 publications
1
30
0
1
Order By: Relevance
“…Second-line treatment for patients with recurrent disease that have been used are vascular endothelial growth factor (receptor) (VEGF(R))-, mammalian target of rapamycin (mTOR)-, and platelet-derived growth factor receptor (PDGFR)-based targeted therapy. These treatments can again induce favorable, however short-lived, responses (Chen and Feng 2019;Italiano et al 2013;Menegaz et al 2018;Tarek et al 2018;Thijs et al 2010). Overall, treatment results in a 5-year overall survival (OS) rate of 15-25%, which shows the high unmet need for novel treatments in DSRCTs (Bent et al 2016;Subbiah et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Second-line treatment for patients with recurrent disease that have been used are vascular endothelial growth factor (receptor) (VEGF(R))-, mammalian target of rapamycin (mTOR)-, and platelet-derived growth factor receptor (PDGFR)-based targeted therapy. These treatments can again induce favorable, however short-lived, responses (Chen and Feng 2019;Italiano et al 2013;Menegaz et al 2018;Tarek et al 2018;Thijs et al 2010). Overall, treatment results in a 5-year overall survival (OS) rate of 15-25%, which shows the high unmet need for novel treatments in DSRCTs (Bent et al 2016;Subbiah et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…O uso de outros agentes também foi relatado. O erlotinibe, um inibidor multialvo da tirosina quinase, levou à resposta parcial em um relato de caso 19 . A atividade contra a doença foi relatada com uso de pazopanibe 20,21 e eribulin 22 .…”
Section: Discussionunclassified
“…In the largest DSRCT comprehensive genomic profile study, no secondary mutation on c-MET was found [ 103 ]. There is a case report of a patient with intra-abdominal DSRCT who received anlotinib, a multi-kinase inhibitor that targets c-Met, for the progressive disease after surgery and first-line chemotherapy showing stable disease for 4 months [ 116 ].…”
Section: Treatmentmentioning
confidence: 99%